2010
DOI: 10.1503/jpn.090099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlations of grey matter reductions in the caudate nucleus of adults with attention deficit hyperactivity disorder

Abstract: Background: Magnetic resonance imaging (MRI) studies have shown decreased caudate volumes in individuals with attention deficit hyperactivity disorder (ADHD). However, most of these studies have been carried out in male children. Very little research has been done in adults, and the results obtained in children are difficult to extrapolate to adults. We sought to compare the volume of the caudate of adults with ADHD with that of healthy controls; we also compared these volumes between men and women. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Reductions in volume and D 2 /D 3 binding potential of the caudate head are a prominent feature in ADHD (Hynd et al, 1993; Montes et al, 2010; Volkow et al, 2007). On tasks requiring conflict anticipation, individuals with ADHD show poor performance, but after MPH administration, performance improves in association with larger changes in caudate D 2 /D 3 binding potential (Fried et al, 2014; Rosa-Neto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in volume and D 2 /D 3 binding potential of the caudate head are a prominent feature in ADHD (Hynd et al, 1993; Montes et al, 2010; Volkow et al, 2007). On tasks requiring conflict anticipation, individuals with ADHD show poor performance, but after MPH administration, performance improves in association with larger changes in caudate D 2 /D 3 binding potential (Fried et al, 2014; Rosa-Neto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced volume and thickness have been noted in other cortical regions, including the occipital cortex (Ahrendts et al, 2011; Proal et al, 2011), parietal cortex [postcentral gyrus (Almeida Montes et al, 2013), inferior parietal (Makris et al, 2007; Proal et al, 2011), precuneus (Proal et al, 2011), superior parietal (Almeida Montes et al, 2013), and temporal pole (Proal et al, 2011). Subcortical regions that are abnormal in adults with ADHD include the caudate (Almeida et al, 2010; Almeida Montes et al, 2010; Onnink et al, 2014; Proal et al, 2011; Seidman et al, 2011), amygdala (Frodl et al, 2010), hippocampus in medicated individuals (Onnink et al, 2014), nucleus accumbens (Seidman et al, 2006), and cerebellum (Biederman et al, 2008). Therefore, studies in adults with persistent ADHD have found brain structural abnormalities that are also seen in childhood (Castellanos et al, 2003; Castellanos and Proal, 2012; Cherkasova and Hechtman, 2009; Frodl and Skokaukas, 2012; Pastura et al, 2011; Peng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies in adults with persistent ADHD have found brain structural abnormalities that are also seen in childhood (Castellanos et al, 2003; Castellanos and Proal, 2012; Cherkasova and Hechtman, 2009; Frodl and Skokaukas, 2012; Pastura et al, 2011; Peng et al, 2013). However, it is notable that most of these studies included samples that were, on average, older than twenty-five years of age (Ahrendts et al, 2011; Almeida et al, 2010; Almeida Montes et al, 2010; Amico et al, 2011; Biederman et al, 2008; Clerkin et al, 2013; Frodl et al, 2010; Hesslinger et al, 2002; Makris et al, 2007; Mattfeld et al, 2014; Onnink et al, 2014; Perlov et al, 2008; Seidman et al, 2011, 2006; Almeida Montes et al, 2013) when most gray matter neuromaturation is complete (e.g., Giedd et al, 1999) and in older samples, gray matter may be reducing due to aging. For example, older adults may actually be demonstrating more rapid reductions in gray matter and white matter compared to younger samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of structural MRI (sMRI) studies have examined correlates of ADHD in adults. A series of reports by Almeida Montes and colleagues has shown that adults with ADHD have reduced cortical thickness in the right superior frontal cortex (Almeida Montes et al 2010) and right frontoparietal cortex (Almeida Montes et al 2012), and that the severity of their ADHD symptoms correlates negatively with thickness in these regions. These reports also reveal reduced grey matter volume in the caudate nucleus (Almeida Montes et al 2010) and, specifically in women, reduced grey matter density in the right cerebellum (Almeida Montes et al 2011) in these individuals.…”
mentioning
confidence: 99%
“…A series of reports by Almeida Montes and colleagues has shown that adults with ADHD have reduced cortical thickness in the right superior frontal cortex (Almeida Montes et al 2010) and right frontoparietal cortex (Almeida Montes et al 2012), and that the severity of their ADHD symptoms correlates negatively with thickness in these regions. These reports also reveal reduced grey matter volume in the caudate nucleus (Almeida Montes et al 2010) and, specifically in women, reduced grey matter density in the right cerebellum (Almeida Montes et al 2011) in these individuals. Other studies have found decreased volume and/or cortical thickness in the orbitofrontal, dorsolateral, and anterior and posterior cingulate regions (Cubillo and Rubia 2010; Makris et al 2007).…”
mentioning
confidence: 99%